A systematic review of studies investigating the effects of controlled whole‐body vibration intervention on peripheral circulation. (29th July 2019) - Mahbub, MH; Hiroshige, Keiichi; Yamaguchi, Natsu; Hase, Ryosuke; Harada, Noriaki; Tanabe, Tsuyoshi
Summary: The findings of the published studies investigating the changes in peripheral circulation induced by exposure to whole‐body vibration (WBV) are not consensual or conclusive. Also, those studies did not consider the role of vibration magnitude on the peripheral circulatory responses making the interpretation of the observed findings difficult. We aimed to review the published literature investigating the effects of controlled WBV intervention on peripheral circulation by characterizing the relevant exposure conditions including vibration magnitudes, and ascertain the specific patterns of responses in peripheral circulation of the lower extremity from such exposure. A computerized search was performed in PubMed and Scopus using selected key search terms, and the relevant data were extracted. The vibration magnitude in the included studies frequently exceeded the limit specified in the International Standard ISO 2631‐1 (1997) for such exposure. As observed, exposure to WBV with frequencies ≤30 Hz caused an improvement in peripheral blood flow (BF) and/or skin temperature (ST) of the lower extremity. In contrast, the responses in BF and ST from exposure to WBV of higher frequencies (31 Hz–50 Hz) produced conflicting results. The findings of this review indicate that WBV exposure with relatively lower frequency and magnitude can be safely and effectively used to induce improvements in peripheral circulation. For this purpose, the limits recommended by the ISO 2631‐1 (1997) should be considered till safe and effective vibration‐related parameters are established.